Transitivity Process and Ideological Construction of Donald Trump's Speeches (NOBEL: Journal of Literature and Language Teaching, 2018)
This research is the collaborative study of Critical Discourse Analysis with the new grammar perspective of Halliday’s Systemic Functional Linguistics Theory focusing on Transitivity System. It investigates the pattern of transitivity process that reveals the linguistic strategies as well as its ideological construction of Donald Trump’s speeches in the 45th United States presidential election. The writer mainly utilizes Fairclough’s framework for CDA which consists of three stages of analysis consisting of description, interpretation, and explanation. Under descriptive-qualitative method, this research significantly gives an understanding about how transitivity processes can be used to reveal the ideology. As the result, Donald Trump uses variety language during his speeches. It is because he applies all the types of transitivity process proposed by M.A.K. Halliday which consists of six types: material, mental, relational, behavioral, verbal, and existential. The transitivity processes eventually reveal that Donald Trump attempts to construct democracy view during his speeches.